Improved VMD‐KFCM algorithm for the fault diagnosis of rolling bearing vibration signals. Issue 4 (1st April 2021) - Chang, Yong; Bao, Guangqing; Cheng, Sikai; He, Ting; Yang, Qiaoling
Abstract: In order to make accurate judgements of rolling bearing main fault types using the small sample size fault data set, a novel approach is put forward that combines particle swarm optimisation kernel fuzzy C‐means (PSO‐KFCM) and variational mode decomposition (VMD). Firstly, by calculating the centre frequency and Pearson correlation coefficient of each mode function of VMD, the decomposition level K of VMD is determined, and the optimal decomposition result is obtained. The singular value decomposition method was used to extract a characteristic value corresponding to the main fault types of bearings from the optimal decomposition results, and faulty feature sample space was established. Then, the kernel function parameters and the initial clustering centre were used as optimisation variables. The PSO algorithm was used to solve the clustering model. The clustering centre of each fault type under the optimal classification result was obtained, and the fault diagnosis model was established. Finally, different fault classification methods are compared, and the conclusions drawn from the experiment show that the method can achieve good results in bearing fault diagnosis. The accuracy of fault classification was improved obviously.